SISTEM APLIKASI MANAJEMEN DATA VENDOR PADA PT. KALBE FARMA – CIKARANG - Komalasari, Yuli; Ukhrowi, Azzarnuji Nur; Adawia, Popon Rabia; Chalimatusadiah, Chalimatusadiah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
In the digital era, fast and open access to information is the key to an organization's success. PT Kalbe Farma, as a leading pharmaceutical company, faces obstacles in providing access to information related to vendor data and employee training. This limitation has an impact on the company's operational efficiency and decision making. Vendors are important business partners in the availability of goods. The right steps are needed in selecting a Vendor so that activities in a company run smoothly. To overcome this problem, a